Decreased Brain Serotonin in rbfox1 Mutant Zebrafish and Partial Reversion of Behavioural Alterations by the SSRI Fluoxetine - Maja R. Adel; Ester Antón-Galindo; Edurne Gago-Garcia; Angela Arias-Dimas; Concepció Arenas; Rafael Artuch; Bru Cormand; Noèlia Fernàndez-Castillo (MDPI AG, 2024)
RBFOX1 functions as a master regulator of thousands of genes, exerting a pleiotropic effect on numerous neurodevelopmental and psychiatric disorders. A potential mechanism by which RBFOX1 may impact these disorders is through its modulation of serotonergic neurotransmission, a common target for pharmacological intervention in psychiatric conditions linked to RBFOX1. However, the precise effects of RBFOX1 on the serotonergic system remain largely unexplored. Here we show that homozygous rbfox1sa15940 zebrafish, which express a shorter, aberrant rbfox1 mRNA, have significantly reduced serotonin levels in telencephalon and diencephalon. We observed that the acute administration of fluoxetine partially reverses the associated behavioural alterations. The hyperactive phenotype and altered shoaling behaviour of the rbfox1sa15940/sa15940 zebrafish could be reversed with acute fluoxetine exposure in the Open Field and the Shoaling test, respectively. However, in the other paradigms, hyperactivity was not diminished, suggesting a distinct intrinsic motivation for locomotion in the different paradigms. Acute fluoxetine exposure did not reverse the alterations observed in the aggression and social novelty tests, suggesting the involvement of other neurological mechanisms in these behaviours. These findings underscore the importance of investigating the intricate working mechanisms of RBFOX1 in neurodevelopmental and psychiatric disorders to gain a better understanding of the associated disorders along with their pharmacological treatment.